Peripheral Lipopolysaccharide Challenge Induces Long‐Term Changes in Tyrosine Hydroxylase Regulation in the Adrenal Medulla. Issue 8 (18th April 2017) - Ong, Lin Kooi; Page, Scott; Briggs, Gabrielle D.; Guan, Liying; Dun, Matthew D.; Verrills, Nicole M.; Dunkley, Peter R.; Dickson, Phillip W.
ABSTRACT: Immune activation can alter the activity of adrenal chromaffin cells. The effect of immune activation by lipopolysaccharide (LPS) on the regulation of tyrosine hydroxylase (TH) in the adrenal medulla in vivo was determined between 1 day and 6 months after LPS injection. The plasma levels of eleven cytokines were reduced 1 day after LPS injection, whereas the level for interleukin‐10 was increased. The levels of all cytokines remained at control levels until 6 months when the levels of interleukin‐6 and ‐4 were increased. One day after LPS injection, there was a decrease in TH‐specific activity that may be due to decreased phosphorylation of serine 31 and 40. This decreased phosphorylation of serine 31 and 40 may be due to an increased activation of the protein phosphatase PP2A. One week after LPS injection, there was increased TH protein and increased phosphorylation of serine 40 that this was not accompanied by an increase in TH‐specific activity. All TH parameters measured returned to basal levels between 1 month and 3 months. Six months after injection there was an increase in TH protein. This was associated with increased levels of the extracellular regulated kinase isoforms 1 and 2. This work shows that a single inflammatory event has the capacity to generate both short‐term and long‐term changes in TH regulation in the adrenal medulla of the adult animal. J. Cell. Biochem. 118: 2096–2107, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The effect of immune activation by lipopolysaccharide on the regulation of tyrosine hydroxylase in the adrenal medulla was studied in vivo. The results show that single peripheral immune activation has the capacity to generate both short and long‐term changes in tyrosine hydroxylase regulation in the adrenal gland of adult rats.